DAMPAK KEBERADAAN PASAR MODEREN TERHADAP LOYALITAS KONSUMEN PADA PASAR TRADISIONAL STUDY KASUS (PASAR KAMPUNG LALANG KECAMATAN MEDAN SUNGGAL) - MELLA YUNITA; KHAMO WARUWU (LP2MTBM MAKARIOZ, 2019)
The purpose of this study was to determine the impact of the existence of modern markets (Indomaret and Alfamart) on consumer loyalty in traditional markets in medan sunggal sub-district. The specific target in this study is traditional market consumers, to be able to maintain customer loyalty, the traditional market needs to work around various ways so that consumers remain loyal in terms of household needs. The existence of modern markets (Indomaret and Alfamart) towards consumer loyalty in traditional markets in medan sunggal sub-district. Involving consumers in answering some questions that have been provided through questionnaires with Likert scale answers. In obtaining the results of the study, a survey of research locations was conducted, distributing questionnaires and then collecting the results of the questionnaires, after which data processing was then evaluated. Through the results of data analysis conducted, various conclusions show that: from the results of the validity test X and Y get r table of 0.975> corrected item total correlation, the Cronbach's Alpha reliability test is 0.789> 0.60 with a reliable meaning while the value of the Cronbach's Alpha reliability test is 0.723> 0.60 is declared reliable. In the test of the coefficient of determination to get an R value of .356 where the presence of a modern market affects 35.6% means that the researcher concludes that there is a significant effect even though it has a relatively low percentage, while the remaining 64.4% can be influenced by other factors outside this research that are not yet known.